2017
DOI: 10.3233/ch-179228
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging as a novel diagnostic tool in microcirculation of wounds

Abstract: Hyperspectral Imaging allowed easy real time determination and visualization of hemodynamically relevant parameters- superficial and deeper oxygen saturation, total hemoglobin and tissue water content. In the patient with scleroderma, acral lesions with decreased perfusion correlated well with necrotic skin aspects.HSI clearly revealed macroscopic conspicuous suture wounds after Dupuytren surgery, infected soft tissue wounds with strong inflammatory hyperemia, edema in burn injuries, spatial geometry of absces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…A spectral dimension that enables spectroscopy, combined with a high spatial resolution suitable for imaging of heterogeneous structures makes hyperspectral imaging relevant for a wide range of biomedical applications [3]. Examples include wound imaging [3][4][5][6][7][8][9][10][11], burn wound imaging [9,12], skin bruises [13], cancer diagnostics and surgical guidance [3,14]. The large amounts of data generated by the technique require methods for extracting relevant information.…”
Section: Introductionmentioning
confidence: 99%
“…A spectral dimension that enables spectroscopy, combined with a high spatial resolution suitable for imaging of heterogeneous structures makes hyperspectral imaging relevant for a wide range of biomedical applications [3]. Examples include wound imaging [3][4][5][6][7][8][9][10][11], burn wound imaging [9,12], skin bruises [13], cancer diagnostics and surgical guidance [3,14]. The large amounts of data generated by the technique require methods for extracting relevant information.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases (n = 19) the multi‐patient studies were reported 1,2,5,7,54‐68 . However, in some cases (n = 12), the case studies were reported 8,50,69‐78 …”
Section: Resultsmentioning
confidence: 99%
“…В зарубежной литературе для исследования ми кроциркуляции во флебологии используют лазерное излучение (L. Huisman) [11], спектральный анализ (G. Daeschlein) [12] (сатурация в поверхностных и более глубоких венах, содержание гемоглобина), од нако работ, посвященных лазерной допплеровской флоуметрии, при поиске в PudMed мы не встретили.…”
Section: Discussionunclassified